Perceived Financial Threat and Psychological Effects on Working Adults in Sarawak During Lockdown for COVID-19 Pandemic - Nurkhalida, Suut; Nasha, Azlan; Muazzin, Awal Din; Jamilah, Jamaluddin; Syaffa, Amin; Rashyid, Aris; Zurraini, Arabi; Chuong, Hock Ting (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia., 2021)
Introduction: The emergence of Coronavirus Disease 2019 (COVID-19) led to the implementation of special mea-sures such as the Movement Control Order (MCO), which in return had caused economic disturbances and psycho-logical effects across many countries over the globe. Objective: Our study aims to determine the perceived financial threat and its predictors, the relationship with psychological outcomes on working adults’ populations in Sarawak during lockdown for the COVID-19 pandemic. Methodsology: We recruited 336 respondents from all divisions in Sarawak through an online survey with sociodemographic data, questionnaires were adapted from the Financial Threat Scale (FTS) to assess the perceived financial threat, and the Depression, Anxiety, Stress Scales 21 (DASS-21) to evaluate the psychological impact of lockdown implementation. IBM SPSS version 23.0 was used for data analysis. A p-value of ≤0.05 was considered statistically significant. Results: The analysis revealed that the employment sector, number of children, and change in income during lockdown were important predictors associated with the per-ceived financial threat. 47.9% of the respondents perceived a moderate-to-severe financial threat. Of these, 72.6% were self-employed, 54.6% were without children and 60.0% had experienced decreased in income during the lockdown. Several factors were identified to be significantly associated with the negative psychological outcomes, namely employment sector, marital status, number of children, and number of liabilities. Generally, a severe per-ceived financial threat was significantly associated with severe levels of depression, anxiety, and stress. Conclusion: There is an urgency to develop strategic plans and policies to provide economic and psychological support for the communities affected by the lockdown and COVID-19 disease.